Influência de aditivos pró-degradantes nas degradações abiótica e biótica do polietileno de alta densidade - Babetto, Alex Sandro (2015)
High density polyethylene (HDPE) is widely used in the manufacture of packaging disposables and in order to minimize the environmental impact caused by disposal, have been incorporated, into the HDPE, additives that promises modify polyethylene chemical structure and promote biodegradation. Chemical modification occurs by oxidative abiotic degradation, accelerated by pro-degrading agents, which decreases the molecular weight and introduces oxygenated organic groups into polyethylene. In this study, iron (Fe) and manganese (Mn) stearate pro-degrading agents were assessed as well as a commercial additive d2w, based on organic salt of manganese, in HDPE films in thermo-oxidative conditions (in an oven at 80°C and 60 °C). The effect of prodegrading agent concentration and oxidation state was assessed on the degradation of HDPE during accelerated weathering (Q-UV), thermomechanical and thermo-oxidative degradation (80 ° C and 60 ° C). Abiotic degradation was assessed by means of infrared spectroscopy, size exclusion chromatography and mechanical properties. Films were also subjected to biodegradation in soil and CO2 content was assessed by respirometric method. The results showed that pro-degrading agents accelerate oxidative degradation. In all degradation processes the abiotic degradation showed to be directly proportional to iron concentration. On the other hand, manganese concentration showed to be inversely proportional to thermo-mechanical degradation and directly proportional to thermo-oxidative degradation and weathering. The oxidation state of iron showed no interference with HDPE degradation, whereas UV radiation significantly enhanced degradation of the polymer. The results show important degradation of previously thermo-oxidated HDPE.